O PREÇO NA CONTRATAÇÃO PÚBLICA: TRIBUNAL DE CONTAS DO ESTADO DE MATO GROSSO DO SUL - Plinio Jose Tude Nakashian (2023)
The subject addressed in the study is focused on the price in public procurement, having as a case study the hiring progress of the Court of Auditors of the State of Mato Grosso do Sul between the years 2020 to 2022. The research carried out aimed to analyze the processes of TCE/MS contracting between the years 2020 at 2022 (October), with a focus on price formation and proximity to the private market price. The method can be defined in two parts, the first being based on an analysis of secondary data extracted from the TCE/MS contracting processes (2020-2022), and, afterwards, bibliometrics and scientometrics were used to deepen the theme price in public contracts in order to understand how it is studied in science. The whole research aims to answer how the TCE/MS can contract with prices close to those practiced in the private market. Fron then on, it was possible to verify the mains factors that lead to the construction of a more efficient reference price, which represents a real gain for the Public Administration and, in the case study, a saving of BRL 6.,204,659.18 (six milion, two hundred and four thousand, six hundred and fifty-nine reais an eighteen cents) to the TCE/MS between the years 2020 and 2022. The research translates relevant information for future studies for the composition of the reference price and the entire process that envelops. Keywords: public procurement; price; cost; economy; efficiency.